Fatty legs : a true story - Jordan, Christy (Annick Press, 2010)
Margaret Pokiak-Fenton tells the story of her experiences as an eight-year-old Inuit girl in a church-run school in Aklavik, Canada, where her strong will made her the target of a mean-spirited nun.